SP0006 CASE 2 DISCUSSANT: LONG TERM EFFICACY OF REMISSION-MAINTENANCE REGIMENS FOR GPA. (June 2019) - Villiger, Peter
Abstract : Background: A case of Giant Cell Arteritis with different visual symptoms and delayed diagnosis will be presented. This 74 year-old patient was pulsed with Glucocorticoids (GC) and thereafter treated with Tocilizumab (TCZ). She rapidly achieved full and lasting remission. After 12 months of treatment with TCZ, infusions were stopped. The patient suffered minor relapse 4 months after treatment discontinuation and again responded to TCZ. The case raises several questions such as: How to dose and how long to treat with TCZ? How to reduce dose and when to stop GC? Are there variables to quantify subclinical diseases activity as CRP and ESR are unreliable under TCZ treatment? Are there predictive factors for relapse after treatment discontinuation? How to control development of disease damage over time? Disclosure of Interests: None declared